Pemetaan Distribusi Kecepatan Arus Saluran Drainase Akibat Pasang Purnama (Spring Tide) Menggunakan HEC-RAS (Studi Kasus Ruas Jalan H. Hassan Alwie - Niaga Barat Kota Samarinda) - Rio Adiputra; Feri Fadlin; Dwi Agung Pramono; Nia Kurniadin (Journal of Geomatics Engineering, Technology, and Science, 2025)
The flow velocity patterns in drainage channels are crucial to study and understand in the context of water and environmental management. Drainage channels play a vital role in conveying rainwater and wastewater, often becoming a limited resource. A deep understanding of the flow velocity patterns in drainage channels is essential to manage water availability, reduce flood risks, and ensure good water quality. These flow velocity patterns are significantly influenced by the geometry, channel topography, water discharge, and other hydrological conditions. Advances in hydraulic modeling technology, such as the use of HEC-RAS software, have enabled more accurate and detailed hydraulic flow simulations. This hydraulic modeling technology is applied to address hydrological issues in the drainage channel on H. Hassan Alwie - Niaga Barat Street, Samarinda City, which frequently experiences water overflow, disrupting mobility and user safety. This study aims to determine the spring tide conditions on the flow velocity distribution in the drainage channel on H. Hassan Alwie - Niaga Barat Street, Samarinda City. Tidal data obtained from the Mahakam River during the spring tide period were used as input in modeling using HEC-RAS 6.5 software. The research results show significant variations in water level and flow velocity in the drainage channel during the spring tide period. The water level reached a maximum of 1.89 meters and a minimum of 0.01 meters, while the flow velocity varied between 0.03 m/s and 0.48 m/s. Mapping the flow velocity distribution revealed clear patterns, with areas of low flow velocity tending to accumulate sediment, potentially causing flooding. These findings provide a better understanding of the interaction between the spring tide phenomenon and urban drainage systems, which can be used to improve drainage planning and management in affected areas.